Variability in performance of agility dogs navigating a dynamic obstacle - Pechette Markley, Arielle; Wood, Moriah K.; Shoben, Abigail B.; Olson, Rachel A. (Frontiers in Veterinary Science, 2024)
IntroductionDuring agility performance, dogs complete a preset obstacle course. The teeter, also known as the seesaw, is the only dynamic contact obstacle. Dogs handle dynamic obstacles differently than static obstacles due to the need for increased coordination and postural control. No studies have been performed evaluating dogs’ abilities or biomechanical strategies to navigate the teeter. The goal of this study was to describe and quantify variability in teeter performance across a sample of dogs of differing body mass and breeds.Materials and methodsTwenty dogs of various body masses and breeds were recruited. Handlers were instructed to line their dog up approximately 5 m from the teeter and to handle the obstacle in a way to best reflect the dog’s typical performance. Repetitions were filmed using a GoPro Hero 11 at 240 frames per second. Data were post processed and footfalls were manually tracked using XMALab. Descriptive statistics were used to describe both central tendency and variability.ResultsMean total obstacle completion time (from dog breaking the plane of the teeter until teeter contact with ground) was 1.31 s (sd = 0.38) and mean total footfalls on the teeter was 18.3 (sd = 3.4). Footfall patterns varied across all phases of teeter performance, with particularly noteworthy variation during descent while the teeter was moving. Some dogs were nearly completely stationary while the teeter dropped while others continued to take steps toward the end of the obstacle as the teeter was in motion. Smaller dogs had more total footfalls and longer teeter completion times than larger dogs, and dogs with a stopped contact behavior took longer to fully exit the teeter after it contacted the ground.DiscussionThese data imply that dogs use a variety of biomechanical strategies to perform a dynamic obstacle. Results of this study provide insight into teeter performance and variables that can be utilized for evaluation in future biomechanical studies. This study also provides initial data on biomechanical strategies used by dogs on dynamic surfaces, which may offer insight into dynamic stability and postural control in dogs and how that may influence injury development during sport.